Culture Condition Improvement for Phytase Production in Solid State Fermentation by Aspergillus ficuum Using Statistical Method. (27th November 2012) - Jafari-Tapeh, H.; Hamidi-Esfahani, Z.; Azizi, M. H.
Abstract : The effective factors on phytase production by Aspergillus ficuum PTCC 5288 were studied using solid-state fermentation method in 250 ml shake flask. The effective process parameters on phytase production were identified using Plackett-Burman design. Four factors were identified of different variables, including glucose, moisture, MgSO4, and fermentation time, which were the most significant. The optimum levels of these significant parameters were determined through response surface methodological approach as follows: 10.14% glucose, 62.69% moisture, 0.46% MgSO4 and 119.23 h. The maximum predicted amount of phytase was 24.33 U/gds and the produced amount of phytase under these conditions was 25.6 U/gds, which indicates the efficacy of the model for prediction of phytase production content under different medium conditions.